Pengaruh Konsep Eco-Friendly terhadap Minat Beli Fore Cafe & Coffee Galaxy Bekasi (International Forum of Researchers and Lecturers, 2025)
Environmental issues are complex and increasingly important. This is also true in the industrial sector, particularly in the culinary industry. Currently, public awareness of environmental issues is increasing, leading consumers to consider eco-friendly factors in their daily lives. The concept of eco-friendliness in the coffee shop industry has become an increasingly popular trend. Especially in the food and beverage (F&B) industry, which plays a significant role in waste production, particularly plastic and food waste. Therefore, the concept of eco-friendly practices has emerged in the F&B industry. This can take the form of using environmentally friendly food ingredients, eco-friendly packaging, and the café concept itself, which conveys an eco-friendly image that can increase consumer purchasing interest. This is implemented by Fore Cafe and Coffee Galaxy Bekasi. This study aims to investigate how the eco-friendly concept is implemented and its impact on consumer purchasing interest at Fore Cafe & Coffee Galaxy Bekasi. The study employs a quantitative approach with a sample and population of 99 consumers of Fore Cafe & Coffee Galaxy Bekasi, selected randomly. The analysis uses validity tests, reliability tests, normality tests, and T-statistical test. The results of the research and data processing using SPSS version 25 showed that the Eco-Friendly concept had an effect on increasing consumer interest in purchasing Fore Cafe & Coffee Galaxy Bekasi, and certainly had a positive effect on environmental conditions.